Brown girl in the ring eaudiobook - Hopkinson, Nalo (Recorded Books, 2001)
In this "impressive debut" from award-winning speculative fiction author Nalo Hopkinson, a young woman must solve the tragic mystery surrounding her family and bargain with the gods to save her city and herself. ( The Washington Post ) The rich and privileged have fled the city, barricaded it behind roadblocks, and left it to crumble. The inner city has had to rediscover old ways—farming, barter, herb lore. But now the monied need a harvest of bodies, and so they prey upon the helpless of the streets. With nowhere to turn, a young woman must open herself to ancient truths, eternal powers, and the tragic mystery surrounding her mother and grandmother. She must bargain with gods, and give birth to new legends. "An impressive debut precisely because of Hopkinson's fresh viewpoint."— The Washington Post